Determination of Fire Damage and Fire Susceptible Areas Using Remote Sensing and Geographic Information Systems: A Case Study Aydıncık (Mersin) District, Türkiye - Fatih Ocak; Feride Cesur; Amira İsmail Aden; Sevim Keklik (Doğal Afetler ve Çevre Dergisi)
As a country located in the Mediterranean climate zone, hundreds of forest fires occur every year in Türkiye and these fires cause many damages. Preventing forest fires is as important as reducing fire damage in reducing this damage. Therefore, areas susceptible to forest fire should be identified before a possible fire, both for early fire detection and early intervention and for reducing destruction. In this context, this study was carried out to determine the damage caused by the forest fire that occurred in Aydıncık district of Mersin in July 2021 and to identify fire-sensitive areas. In the first part of the study, NDVI (Normalized Difference Vegetation Index), NBR (Normalized Burn Ratio) and dNBR (Differenced Normalized Burn Ratio) indices were calculated using Landsat 8 OLI/TIRS satellite images to determine the difference between before and after the fire with Remote Sensing (RS) techniques. In the second part of the study, forest fire susceptibility areas were identified, and a Geographic Information Systems (GIS) supported forest fire susceptibility map of Aydıncık district was created. According to the NDVI index, it was determined that bare land and settlements increased from 13.43% in 2020 to 23.02% in 2021, and there was a decrease in areas with different forest densities. According to the dNBR index results, it was determined that 27.67% (12,153.83 ha) was moderately-highly damaged by fire and there were losses in areas with different plant densities. In addition, according to the forest fire susceptibility analysis, it was determined that the area showed 7.82% very low, 22.46% low, 28.65% medium, 28.56% high and 12.50% very high susceptibility.